2020
DOI: 10.47067/real.v3i1.22
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Application of Natural Dyes on Natural Fibers: An Eco-Friendly Perspective

Abstract: Dyes derived from natural resources like plant leaves, roots, bark, fruits, stem, insect secretions, and minerals were the only dyes available in the history of mankind for dyeing textiles. The first discovery of the synthetic dyes dates back to 1856.Due to the industrialization and globalization, the use of the synthetic dyes has increased in past century. The variety in hue, shades and economic benefits of synthetic dyes have declined gradually and slowly. However, the environmental threats and health hazard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Color Strength and Color Difference: Color strength (K/S) values of the samples were determined using the Kubelka-Munk formulation (Equation (1), where R: the decimal fraction of the reflectance of fabric, K: the absorption coefficient, S: the scattering coefficient), which was programmed in a Minolta 3600d Spectrophotometer (illuminant D65, 10 standard observers) based on reflectance measurements. The color difference in the treated sample compared to untreated fabric was evaluated using the L*, a* and b* coordinate values according to CIELAB; see Equation (2).…”
Section: Pad-dyeing and Finishing Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Color Strength and Color Difference: Color strength (K/S) values of the samples were determined using the Kubelka-Munk formulation (Equation (1), where R: the decimal fraction of the reflectance of fabric, K: the absorption coefficient, S: the scattering coefficient), which was programmed in a Minolta 3600d Spectrophotometer (illuminant D65, 10 standard observers) based on reflectance measurements. The color difference in the treated sample compared to untreated fabric was evaluated using the L*, a* and b* coordinate values according to CIELAB; see Equation (2).…”
Section: Pad-dyeing and Finishing Processmentioning
confidence: 99%
“…Textile dyeing processes consume excessive amounts of water and leave a large amount of untreatable hazardous waste, such as salts, hydroxides and unreacted dyes, in the environment. Environmental pollution associated with the textile industry is seen as a critical global problem and new technologies and alternative environmentally friendly processes need to be developed to alleviate this situation [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic dyes are detrimental for health and have some hazardous impacts on the environment as well [2,3]. Natural dyes have emerged as an eco-friendly solution to the textile industries [4,5] due to their diverse shades on textile fibers [6] and fabric [7]. They can be extracted from natural resources like plants [8,9], herbs [10], fungi [11], lichens [1], minerals [12], insects [12] and different tissue cultures of animals [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Guha et al wrote in their review paper about various sources of natural dyes and their applications, but discussed only a handful of sources of collection and fields of application [13]. Ahsan et al reported on the extraction and the application of natural dyes, but have not clearly discussed any of the extraction processes [14]. Samanta et al reviewed a chapter about the application of natural dyes in textile fabrics.…”
Section: Introductionmentioning
confidence: 99%